Determinación de los hábitos de desayuno de estudiantes universitarios según el lugar donde viven.: Breakfast Habits of University Students - özkaya, ismail (Nutrición Clínica y Dietética Hospitalaria, 2021)
This research is planned to determine the breakfast habits of students studying at Kırklareli University. 51% of the students (n = 1200) are male and 49% are female. The research data were collected with the help of a questionnaire using face-to-face interview technique, and the questionnaire prepared by the researchers included information about demographic characteristics, place of residence, disease information, breakfast habits, water and food-beverage consumption frequency, and foods consumed at breakfast. No significant difference was found between male and female students in terms of Body Mass Indexes. It was determined that 49% of the students stayed in the dormitory/sorority, 28% stayed in the student house, 23% lived with their family. When breakfast habits are examined; It was determined that 73% of students had breakfast and 27% did not have regular breakfast. Also, the habit of having irregular breakfast is the most common in staying in the student house, and the habit of having the most regular breakfast in the state dormitory/sorority. For this reason, breakfast service should be offered in school cafeterias especially in the student house and soups should be sold in canteens, especially in winter. Educational activities such as seminars and conferences on nutrition should be organized and researches including cognitive and behavioral tests should be conducted to determine the effect of breakfast meal on students’ cognitive performance. Keywords: Nutritional Habbits, Breakfast Habbits, Breakfast Preferences, University Student